The Role of Social Context in Live Streaming Commerce – An Interpersonal Perspective - Ding, Jia; Wang, Yijing; Laufer, Daniel (Emerald, 2026)
Purpose In the dynamic arena of live streaming commerce, the influence of other viewers has surged to the forefront, marking a significant component of the social context. This study ventures into the interpersonal dynamics within live streaming commerce by delving into the effects of two factors – social presence and group identity salience – on consumer attitudes. Design/methodology/approach Two between-subject experiments were conducted to collect data. The hypotheses were verified by analysis of variance (ANOVA) and PROCESS macro. Findings Our findings reveal that higher social presence leads to positive persuasive outcomes, whereas the influence of group identity salience appears to be negligible. Crucially, the results demonstrate that attitudinal persuasion knowledge mediates the impact of social presence on consumer attitudes, shedding light on the underlying processes that govern consumer responses in the context of live streaming commerce. Originality/value To the best of the authors’ knowledge, this research is one of the first to investigate the heightened visibility of viewers within live streaming commerce, contributing to a nuanced perspective on the instrumental role of social context in driving consumer decision-making processes.
Keywords: 35 Commerce, Management, Tourism and Services; 3503 Business Systems In Context; 3506 Marketing; 1505 Marketing; 1506 Tourism; 1507 Transportation and Freight Services; 3506 Marketing; 3507 Strategy, management and organisational behaviour; 3508 Tourism; Social presence; Group identity salience; Live streaming commerce; Persuasion knowledge; Interpersonal perspective